Newstech kiosk machine - Jauhari, Wardina Haidi; Md Sharif, Arini Atira; Mohd Sufian, Nurul Huda; Abdul Aziz, Nadiatul Izzah (Universiti Teknologi MARA, Kedah, 2019)
Often, newspaper delivery arrives later than the library operation hours. Thus, to avoid patrons from waiting too long, newstech kiosk machine assist library patrons to print newspapers by themselves, without requiring assistance from librarians by choosing their favourite newspaper according to their respective choices. Creative, innovative and hassle-free!